PENGARUH CURRENT RATIO (RASIO LANCAR), RETURN ON EQUITY DAN TOTAL ASSET TURN OVER (TATO) TERHADAP HARGA SAHAM PADA SECTOR CONSUMER GOODS INDUSTRY DI BURSA EFEK INDONESIA - Monika Luis Gultom; Dianty Putri Purba; Zepria Zepria; Resta Sinaga (JURNAL GLOBAL MANAJEMEN, 2019)
This research aimed at testing and analyzing the effect of current ratio, return on equity and total asset turn over on stock price in Indonesia Stock Exchange. This research applied quantitative approach with descriptive method. This research was an explanatory research. The sample of this research was twelve (12) consumer goods industry companies which met the criteria. To prove the hypothesis, this research applied Double Linear Regression model which used T test (partially) and F test (simultaneously). This research showed that current ratio, return on equity and total asset turn over simultaneously had effect on consumer goods industry sector stock price in Indonesia Stock Exchange. Partially current ratio and return on equity had positive and significant effect on stock price, meanwhile total asset turn over partially did not have significant effect on stock price. The result of determination coefficiency showed that Ajusted R2 value had variation of stock price variable which could be explained by current ratio, return on equity and total asset turn over which was as much as 52%, while the rest was as muc as 42% explained by other variation of variable.